Enhancing Public Accountability through AIS Audits in Tegal Regency - Wisnu (Scimadly Publishing, 2025)
This study examines the role of accounting information system (AIS) audits in fraud control within the Tegal Regency Local Government. The research synthesizes findings from multiple empirical studies conducted between 2021 and 2025, focusing on the interaction between AIS, internal control, internal audit, and transparency in preventing fraudulent practices. Results indicate that effective AIS audits strengthen internal control mechanisms, enhance data accuracy, and improve financial accountability. Empirical evidence shows that well-designed AIS can minimize opportunities for manipulation and misappropriation, aligning with the fraud triangle theory that links fraud occurrence to pressure, opportunity, and rationalization. The findings also highlight that digital-based auditing practices and good governance contribute significantly to building transparency and public trust. Some studies report mixed results regarding the mediating effect of internal control on AIS and audit roles. This implies that fraud prevention effectiveness depends on institutional readiness, auditor competence, and system integration. The study recommends that the Tegal Regency Local Government adopt integrated, transparent, and digitalized audit mechanisms to enhance fraud detection and prevention capacity. Future research should include broader regional comparisons and evaluate the long-term impact of AIS audit reforms on governance performance.